ANALYSIS PLAN ON BUYING A NEW MACHINE PRINTING COMPANY CV. KLATEN FRIEND TO INCREASE PROFIT - Dwiastuti, Maria Magdalena Pur (Accounting, 2010)
In the current economic conditions as not all companies are established to achieve the results as expected. Therefore, companies must be able to anticipate any kind of changes that occur involving corporate life. One of the things that must be considered in order to grow is an investment company. Many ways can be done to take investment decisions, among others, with the purchase of new machinery. The purchase of new machines in addition to cost concerns or benefits are also expected to increase company profit. Keyword : Machine, Profit, Company.